2017
DOI: 10.1063/1.4993583
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on exciplex pumped alkali vapor lasers with sonic-level gas flow

Abstract: Considering the effects of higher excited and ion energy states and utilizing the methodology in the fluid mechanics, a modified model of exciplex pumped alkali vapor lasers with sonic-level flowing gas is established. A comparison of output characters between subsonic flow and supersonic flow is made. In this model, higher excited and ion energy states are included as well, which modifies the analysis of the kinetic process and introduces larger heat loading in an operating CW exciplex-pumped alkali vapor las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To solve the above problem, flowing gas system has been introduced for high power DPAL [10][11][12][13]. In these flowing systems, the gas velocity in a tubular metal pipe can get to be more than 10 m/s by using a blower.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above problem, flowing gas system has been introduced for high power DPAL [10][11][12][13]. In these flowing systems, the gas velocity in a tubular metal pipe can get to be more than 10 m/s by using a blower.…”
Section: Introductionmentioning
confidence: 99%
“…More recent detailed modelling of alkali laser systems [9,[14][15][16] indicated the need to significantly expand both the number of species and number of reactions in the BLAZE simulations. As such the model was expanded to also include Xe, Cs(6 2 D 3/2 ), Cs(6 2 D 5/2 ), Cs(7 2 P 1/2 ), Cs(7 2 P 3/2 ), Cs(8 2 S 1/2 ), CsXe(X 2 Σ + 1/2 ), CsXe(A 2 Π 1/2 ), CsXe(A 2 Π 3/2 ), CsXe(B 2 Σ + 1/2 ), Cs + , and Cs 2 + for a total of 21 species and 39 reactions, appendix A.…”
Section: Kineticsmentioning
confidence: 99%
“…A constant Penning ionization rate of 4 × 10 −14 m 3 s −1 [25] was used in this work, appendix A. Note that the Barbier rates [25] are for Rb rather than Cs and that the value for the states of interest were closer to the value of 4×10 −14 m 3 s −1 , rather than the constant value of 1 × 10 −14 m 3 s −1 used in other works [14,16,26]. Recombination reactions [14,27,28] that result in the creation of Cs 2 + were also added to the model.…”
Section: Ionization and Recombination Reactionsńmentioning
confidence: 99%
“…The results showed that due to the high heat loading generated by multiple transitions, a sharp temperature gradient occurs in the cell, which may cause the experimental device to melt down and the stimulated emission to quench. Therefore, they introduced gas flow into the system to reduce the temperature gradient [13] and applied fluid methods to the CW XPAL system, with good simulation results being achieved [14] . In another approach, Yacoby et al performed in-depth fluid dynamic studies of alkali vapor lasers with super-fast gas flows [15,16] .…”
Section: Introductionmentioning
confidence: 99%